A Bearded Indian Female: A Rare Presentation of Cushing’s Syndrome - Jain, Rajesh; Madhu, SV; Kant, Saket; Prakash, Ved; Kumar, Vinod (Journal of the ASEAN Federation of Endocrine Societies, 2014)
A 16-year-old Indian girl presented with increased facial hair growth, weight gain, amenorrhea and generalized weakness for the last 3 months. On examination she was found to have severe hirsutism, her modified Ferriman-Gallwey score was 24/36, she had broad purple striae on abdomen, hypertension and proximal myopathy. On investigations, the patient was found to have ACTH dependent Cushing’s syndrome